Endoscopic ultrasound-guided radiofrequency ablation for treatment of pancreatic neuroendocrine tumors: Multicenter prospective study - Rizzatti, Gianenrico; Napoléon, Bertrand; Caillol, Fabrice; Crinó, Stefano Francesco; de Nucci, Germana; Pham, Khanh Do-Cong; Giovannini, Marc; Leblanc, Sarah; della Torre, Silvia; Palazzo, Laurent; Pafundi, Pia Clara; Conti Bellocchi, Maria Cristina; Spada, Cristiano; Larghi, Alberto (Endoscopy International Open, 2025)
Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) has been proposed as a minimally invasive alternative to surgery for treatment of both functional (F-) and non-functional (NF-) pancreatic neuroendocrine tumors (PanNETs). We performed a large prospective multicenter study to evaluate safety and effectiveness of EUS-RFA in patients with F- and NF-PanNETs.Patients with F- (≤ 2 cm) and NF-PanNETs (15 mm-25 mm) were prospectively enrolled over a 43-month period. The primary aim was safety, defined as rate of adverse events (AEs). The secondary aim was effectiveness defined as complete disappearance of the hormonal secretion syndrome in F- PanNETs, whereas for NF-PanNETs, complete response was defined as absence of enhancing tissue and of detectable lesion at magnetic resonance imaging/computed tomography scan and Gallium-positron emission tomography, respectively. The EUSRA 19G needle was used in all patients. After treatment completion, follow-up was performed for 1 year.During the study period, a total of 60 patients were enrolled, 30 with insulinomas and 30 with NF-PanNETs (mean lesion size 14.5 ± 4.5 mm). In 78.3% of patients, a single RFA session was performed. Overall, AEs occurred in nine of 60 patients (15%), in four patients (13.3%) with insulinomas and in five (16.7%) with NF-PanNETs, with only one severe AE. Complete insulin hypersecretion symptom resolution was obtained in 29 of 30 patients (96.7%) with insulinomas, whereas for NF-PanNETs, complete radiological response was obtained in 22 of 25 patients (88%) with long-term follow up.Our prospective international multicenter study demonstrated that EUS-RFA is highly safe and effective for the treatment for both F- and NF-PanNETs.
Keywords: Endoscopic ultrasonography; Pancreas; Intervention EUS; Endoscopy Upper GI Tract; RFA and ablative methods